PENENTUAN TINGKAT BAHAYA EROSI DALAM RANGKA MENENTUKAN PRIORITAS REHABILITASI LAHAN DI BUKIT TANGKILING, KALIMANTAN TENGAH (The Erosion Levels in Order to Determine the Rehabilitation Priority in Bukit Tangkiling, Central Kalimantan): Yusintha Tanduh, Rosdiana, Nursiah - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2015)
ABSTRACTThe Nature Recreation Parks of Bukit Tangkiling is placed at the Bukit Batu Sub-District, Palangka Raya City, it has the variation of topography that dominated by vegetables (agriculture crops), scrub, bushes, and secondary forest. Its site must be managed carefully in order to totality conservation of biodiversity and its landscape. The aim of this research is to calculate the erosions at the each site of the Bukit Tangkiling Nature Recreation Parks and also it make the distribution map of erosion. The research using USLE method (Wishmeier dan Smith, 1978). Research result showed that vegetables at the site consist of string bean, eggplant, cassava, etc. There were wild-grassland and critical lands that be caused by annual dry-season. The mean annual precipitation namely 27.453 cm, with its maximal at the December namely 45.73 cm; and its minimal at the August, namely 12.08 cm. The mean rains namely 16.9479 days per month with its maximal at the December, namely 24.87 day per month; and its minimum at the September, namely 8.75 day per month. The high value of length and slope is 3.389867 that resulted by vegetable of string bean whereas the lowest value is 1.796597 that resulted by the critical land. The value of management plants and conservation action are 0.7 to 1. Keywords: Erosion, conservation, Bukit Tangkiling, vegetables